Analisis pengaruh ekspor, kurs dan utang luar negeri terhadap cadangan devisa Indonesia - Ayu Bake, Putri; Hodijah, Siti; Nurjanah, Rahma (e-Journal Perdagangan Industri dan Moneter, 2024)
The purpose of this research is to find out and analyze the development of exports, exchange rates, foreign debt and foreign exchange reserves in Indonesia as well as the effect of exports, exchange rates and foreign debt on foreign exchange reserves in Indonesia. This research uses descriptive and quantitative analysis methods. The data used is secondary data of the time series type from 1987-2022, which comes from the World Bank, the Central Statistics Agency and Bank Indonesia. Data is analyzed using the Error Correction Model (ECM) analysis tool. The results showed that the average development of Indonesia's foreign exchange reserves was 9.72%, the average development of Indonesia's exports was 9,44%, the average development of Indonesia's exchange rate was 10.13%, and the average development of Indonesia's foreign debt was 6,15%. Based on the results of long-term regression, it is known that exports and foreign debt have a significant effect on Indonesia's foreign exchange reserves, while the exchange rate does not have a significant effect on Indonesia's foreign exchange reserves in the long term. Then the results of short-term regression are known that exports and foreign debt have a significant effect on Indonesia's foreign exchange reserves, while the exchange rate does not have a significant effect on Indonesia's foreign exchange reserves in the short term.